Veriﬁcation and validation of digital twins and virtual testbeds - Ulrich Dahmen; Tobias Osterloh; Jürgen Roßmann (International Journal of Advances in Applied Sciences, 2022)
Our society is surrounded by technical systems that increasingly inﬂuence andtake over aspects of everyone’s everyday life. As we build on the correct functioning, the need for appropriate methodologies that support the development of reliable products persists. However, the development and in particular the qualiﬁcation become challenging due to their increasing inherent complexity. Virtual testbeds and digital twins are modern key concepts in this context and offer a wide range of opportunities for simulation-based veriﬁcation and validation processes with virtual prototypes, especially in cases where real tests are hard to perform. However, the validity of test results derived from virtual experiments depends on the quality of the underlying simulation models.Of course, the models themselves must be veriﬁed before. But in the contextof virtual testbeds and digital twins this becomes challenging since the corresponding models are usually complex themselves. Therefore, we presented an approach to establish structured veriﬁcation and validation activities for digital twins and virtual testbeds, based on a modular conﬁguration framework that supports the development of complex simulation models.